Ability of Garlic and Ginger Oil to Reduce Salmonella in Post-Harvest Poultry - Kelsy Robinson; Anna L. F. V. Assumpcao; Komala Arsi; Annie Donoghue; Palmy R. R. Jesudhasan (Animals, 2022)
Approximately 1.35 million human salmonellosis cases are reported in the United States every year, resulting in over 26,000 hospitalizations and 400 deaths. Consumption of contaminated poultry products is one of the leading causes of human salmonellosis. Poultry meat becomes contaminated when feces from an infected bird comes into contact with the carcass during processing. Additional carcasses can then become cross-contaminated along the processing line. While chemicals such as peracetic acid are currently used to kill microbes such as Salmonella, consumers are increasingly calling for more natural alternatives. Our objective for this study was to determine the ability of the phytochemicals garlic and ginger oil to reduce Salmonella prevalence in the processing environment. In a simulated scalding tank environment, dipping contaminated chicken skin samples in a solution containing both garlic and ginger oil reduced Salmonella by up to 2 log CFU. Furthermore, the oils prevented Salmonella growth in the tank solution. The mechanism of action of garlic and ginger was evaluated using the sub-inhibitory concentration of each oil individually. While both were found to decrease autoinducer-2 (AI-2) levels, no effect was seen on expression of 10 genes involved in Salmonella virulence and survival. In total, this work demonstrates the potential of garlic and ginger to reduce Salmonella prevalence in the post-harvest environment. However, more work remains to be done to understand the mechanism of action.